The link among two pro-inflammatory syndromes of these days: sepsis and obesity - Terra, Fernanda; Terumi, Marcelli; Bottura, Guilherme; Geise, Bruno; Câmara, Niels Olsen Saraiva; Latancia, Marcela (Revista de Medicina, 2014)
Several studies shows that patients with obesity have more chance to develop sepsis, moreover they possess a higher risk of mortality. Sepsis, which is a systemic infection, that culminates in modulation of cell activation and secretion of pro-inflammatory cytokines. In addition, obesity, now acknowledged as a metabolic syndrome, described as pro-inflammatory as well. This review aims to clarify and point out the relations between two disturbing syndromes of modern times.